Mutational analysis of a phenazine biosynthetic gene cluster in Streptomyces anulatus 9663 - Saleh, Orwah; Flinspach, Katrin; Westrich, Lucia; Kulik, Andreas; Gust, Bertolt; Fiedler, Hans-Peter; Heide, Lutz (Beilstein Journal of Organic Chemistry, 2012)
The biosynthetic gene cluster for endophenazines, i.e., prenylated phenazines from Streptomyces anulatus 9663, was heterologously expressed in several engineered host strains derived from Streptomyces coelicolor M145. The highest production levels were obtained in strain M512. Mutations in the rpoB and rpsL genes of the host, which result in increased production of other secondary metabolites, had no beneficial effect on the production of phenazines. The heterologous expression strains produced, besides the known phenazine compounds, a new prenylated phenazine, termed endophenazine E. The structure of endophenazine E was determined by high-resolution mass spectrometry and by one- and two-dimensional NMR spectroscopy. It represented a conjugate of endophenazine A (9-dimethylallylphenazine-1-carboxylic acid) and L-glutamine (L-Gln), with the carboxyl group of endophenazine A forming an amide bond to the α-amino group of L-Gln. Gene inactivation experiments in the gene cluster proved that ppzM codes for a phenazine N-methyltransferase. The gene ppzV apparently represents a new type of TetR-family regulator, specifically controlling the prenylation in endophenazine biosynthesis. The gene ppzY codes for a LysR-type regulator and most likely controls the biosynthesis of the phenazine core. A further putative transcriptional regulator is located in the vicinity of the cluster, but was found not to be required for phenazine or endophenazine formation. This is the first investigation of the regulatory genes of phenazine biosynthesis in Streptomyces.
Keywords: phenazine; gene cluster; gene inactivation